Perencanaan Unit Biodigester Skala Rumah Tangga Untuk Pemulihan Biogas Di Kelurahan Sekeloa, Kota Bandung - Sulaeman, Riza Azrilla; Muhammad Irham Anshari; Karennina Resaryana Eka Putri; Sekar Arum Fajriyanti; Mila Dirgawati (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), 2024)
Waste is one of the environmental problems in Bandung City. RT 05 RW 04 Sekeloa Village, Bandung City has a waste problem in its environment in the form of accumulation of waste caused by the difficulty of road access and the diverse topographical conditions of the area so that the transportation process does not run well. This research aims to plan biodigesters technology from organic waste so that it can minimize waste accumulation and provide benefits to local residents. This research was conducted by collecting observations, questionnaires, and analyzing the technical and non-technical aspects of waste management in RT 05 RW 04. From the analysis, it was found that the biodigester volume that can be used is 8.49 m3 with a diameter of 3 m, and a height of 1 m with a capacity to process organic waste of 113 kg / day. The designed biodigester is able to serve 178 people out of 222 people in RT 05 RW 04. With this biodigester technology, it is expected to reduce the use of LPG gas to 135 kg with a nominal value of Rp.2,970,000 every month